Analysis of Work Loyalty and Work Motivation during the Covid-19 Pandemic on Employee Performance on Delivery Services in Palembang City - Trisninawati, Trisninawati; Noviardy, Andrian; Zulfikri, Kemas (Asia Pacific Journal of Management and Education (APJME), 2023)
This study aims to determine the performance of employees who are influenced by work loyalty and work motivation at the Delivery Service Service in Palembang City during the Covid-19 Pandemic, totaling 40 respondents. Purposive sampling was used in this research sample and a survey was conducted to collect data through a questionnaire with a Likert scale and using multiple regression analysis with a significance level of 5% analysis of the data This study found that work loyalty and work motivation have a positive effect on employee performance with the F value obtained at 6.550 which is greater than F table (3.24), this is also strengthened by the significant level value of 0.004 or the significance obtained is smaller than = 0.05. The results of the t-test of work loyalty show 0.231 > 0.05, which show that work loyalty has no effect on employee performance. The results of the t-test of work motivation show a t-statistic value of 0.004 <0.05, which show motivation partially has a significant influence on employee performance. Thus the multiple regression model can be used to predict employee performance in Delivery Services in Palembang City.